2009
DOI: 10.1055/s-0029-1215872
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Temporomandibular Joint Disorders

Abstract: The temporomandibular joint (TMJ) has many essential functions. None of its components are exempt from injury. Facial asymmetry, malocclusion, disturbances in growth, osteoarthritis, and ankylosis can manifest as complications from trauma to the TMJ. The goals of initial treatment include achievement of pretraumatic function, restoration of facial symmetry, and resolution of pain. These same objectives hold true for late repairs and reconstruction of the TMJ apparatus. Treatment is demanding, and with opposing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 65 publications
2
32
0
1
Order By: Relevance
“…OA of the TMJ in humans is usually caused by wear and tear leading to osteophytosis (Matsuura et al, 2001;Giannakopoulos et al, 2009). In humans, degenerative OA is an agerelated disease with the severity of osseous changes in the condylar head and mandibular fossa increasing with age (Alexiou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…OA of the TMJ in humans is usually caused by wear and tear leading to osteophytosis (Matsuura et al, 2001;Giannakopoulos et al, 2009). In humans, degenerative OA is an agerelated disease with the severity of osseous changes in the condylar head and mandibular fossa increasing with age (Alexiou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Direct trauma to the mandible producing condylar fractures, sub condylar fractures, other mandibular fractures, or no fractures has been implicated as one of the initiating factors of osteoarthritis. Trauma to the mandible can induce a joint effusion acutely [31,32]. Harris et al studied 13 patients who had sustained trauma to the mandible and found abnormal uptake in their TMJ scintiscans [33].…”
mentioning
confidence: 99%
“…Also, Seligman and Pullinger showed in a multiple stepwise logistic regression analysis that trauma history is a moderate differentiating feature in patients with intracapsular TMJ disorder [35]. Due to the complex and multifactorial etiology of this particular disease process, the actual incidence of osteoarthritis directly related to trauma to the mandible is difficult to determine, especially in traumatic events that do not result in fractures [31]. The existing literature reports a wide range.…”
mentioning
confidence: 99%
See 2 more Smart Citations